2003
DOI: 10.1007/s00439-003-0919-3
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of fetal DNA persistence in maternal plasma after pregnancy

Abstract: Short-and long-term persistence of fetal DNA in maternal plasma has been investigated. Short-term persistence at very low concentration was detected in 47 out of 105 women within two days after delivery. Twelve out of 13 samples re-tested within three days scored negative.No long-term persistence was detected in 172 women who had previous sons or abortions. Molecular microchimerism due to circulating fetal DNA persisting from previous pregnancies should not hamper non-invasive plasma-based prenatal testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 5 publications
(9 reference statements)
1
22
0
1
Order By: Relevance
“…The available data in literature about fetal microchimerism within same species, especially in women, are also contradictory. Numerous publications provided data about fetal microchimerism after pregnancy in women [for details, see review (Gammill and Nelson 2010)], but studies claiming no evidence for fetal DNA in maternal plasma after delivery were also published (Lo et al 1999; Smid et al 2003). Our results based on three different methods suggest that beside the prominent role of placentation, the influence of species-specific differences in pregnancy-related microchimerism cannot be ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…The available data in literature about fetal microchimerism within same species, especially in women, are also contradictory. Numerous publications provided data about fetal microchimerism after pregnancy in women [for details, see review (Gammill and Nelson 2010)], but studies claiming no evidence for fetal DNA in maternal plasma after delivery were also published (Lo et al 1999; Smid et al 2003). Our results based on three different methods suggest that beside the prominent role of placentation, the influence of species-specific differences in pregnancy-related microchimerism cannot be ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…The first report studied eight patients delivered by elective CS with serial samples taken immediately postpartum, and all but one had cleared cff DNA by 2 h. The mean half-life calculated from these eight patients was 16.3 min (ranging from 4 to 30 min) (Lo et al, 1999a). A much larger investigation of postpartum persistence of fetal DNA did not report any data relating to the mode of delivery (Smid et al, 2003). In that study, 47/105 of women tested positive within 2 days of delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Free fetal DNA rises in concentration following elective termination of pregnancy (Wataganara et al, 2005) and preterm labor (Leung et al, 1998), but the labor process at term does not appear to cause a rise in cff DNA concentration (Ingargiola et al, 2003). The largest study of postnatal clearance to date found that 45% of women still had detectable DNA on day 1-2 postpartum (Smid et al, 2003), but information regarding the exact time interval to testing and the mode of delivery was not reported. To our knowledge, data directly comparing clearance rates in women according to the presence or absence of labor have not been previously published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Moreover, most reports have suggested that cell-free fetal DNA is unlikely to persist in maternal plasma. [12][13][14] Similar to the circulating fetal DNA, circulating fetal-derived hPL RNA has recently been shown to be cleared rapidly from the maternal plasma after delivery with the clearance half-life of 14.1 min. 11 The rapid clearance of the fetal nucleic acids suggests that prenatal diagnosis performed using fetal DNA and RNA in maternal plasma is unlikely to be susceptible to false results due to previous pregnancies.…”
Section: Post-delivery Clearancementioning
confidence: 99%